Multi Parametric Access Control System for Multiple Zones - Dweik, Lama; Abusara, Nahid (Palestine Polytechnic University - Department of Computer Engineering)
Over the years, access control systems have become more and more sophisticated. Today, the term "access control system" most often refers to a computer-based, electronic card access control system. The electronic card access control system uses a special "access card", rather than a brass key, to permit access into the secured area. Access control systems are most commonly used to control entry into exterior doors of buildings. In this project the system is designed for the University. This access control system will control the access to the University campus and buildings. The purpose of an access control system is to provide quick, convenient access to those persons who are authorized, while at the same time, restricting access to unauthorized people. Moreover, this system will provide different levels of authorizations and will allow users to enter only during duty times and days. The user can use either his/her magnetic card or using Bluetooth enabled device to identify his/her identity. The system will also have a fire detection feature, an MQ CO2 gas sensor will be used to detect any fires, if a fire was detected all doors will be opened.
CD , Number of page 110, هندسة حاسوب 7/2014
Keywords: Multi , Parametric , Access , Control , System , Multiple , Zones